Estado de la enseñanza del español como lengua extranjera en Santander - Quintero, Luz Mary (Colombian Applied Linguistics Journal, 2014)
This article presents partial results of a research project about the current state of Spanish as a foreign language in Santander between 2000 and 2011. Data were gathered by interviewing teachers and directives from the participating institutions. Besides, some documents that socialize teaching experiences were also collected. Findings show that there are few teaching experiences in Spanish as a foreign language in Santander, most of the experiences that were identified have taken place in Bucaramanga and Barrancabermeja in a lower proportion. It was also found that that there are no previous researches that give account of the field in the region. Finally, methodologies, didactic materials and evaluation and assessment processes are always selected or adapted depending on the learners’ interests and needs.